Breaking the myth that relay swimming is faster than individual swimming - Skorski, S.; Etxebarria, N.; Thompson, K. G. (International Journal of Sports Physiology and Performance, 2016)
To investigate if swimming performance is better in a relay race than in the corresponding individual race.